Core competencies for scientific editors of biomedical journals: consensus statement - Moher, David (BMC Med, 2017)
BACKGROUND: Scientific editors are responsible for deciding which articles to publish in their journals. However, we have not found documentation of their required knowledge, skills, and characteristics, or the existence of any formal core competencies for this role. METHODS: We describe the development of a minimum set of core competencies for scientific editors of biomedical journals. RESULTS: The 14 key core competencies are divided into three major areas, and each competency has a list of associated elements or descriptions of more specific knowledge, skills, and characteristics that contribute to its fulfillment. CONCLUSIONS: We believe that these core competencies are a baseline of the knowledge, skills, and characteristics needed to perform competently the duties of a scientific editor at a biomedical journal.